2016
DOI: 10.1111/jcmm.12791
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of EZH2 expression in patients with oesophageal cancer: a meta‐analysis

Abstract: Enhancer of zeste 2 (EZH2), a key component of polycomb repressive complex 2 (PRC2), was of great importance in human cancer pathogenesis. Various studies examined the relationship between EZH2 overexpression with the clinical outcome in patients with digestive cancers, but yielded conflicting results. Electronic databases updated to January 2015 were searched to find relevant studies. A meta‐analysis was conducted with eligible studies which quantitatively evaluated the relationship between EZH2 overexpressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 30 publications
(32 reference statements)
0
10
0
1
Order By: Relevance
“…Previous studies revealed that the EZH2 gene participated in cellular growth regulation (6,7). The mechanism underlying the function of EZH2 function was the inhibition of the Wnt signaling pathway in chromatin and the promotion of cell proliferation (7,8).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies revealed that the EZH2 gene participated in cellular growth regulation (6,7). The mechanism underlying the function of EZH2 function was the inhibition of the Wnt signaling pathway in chromatin and the promotion of cell proliferation (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies revealed that the EZH2 gene participated in cellular growth regulation (6,7). The mechanism underlying the function of EZH2 function was the inhibition of the Wnt signaling pathway in chromatin and the promotion of cell proliferation (7,8). Furthermore, as a transcription inhibition factor, EZH2 influenced the activity of multiple genes at the gene level; most notably, it inhibited tumor metastasis genes (including phosphoinositide, protein kinase B and matrix metalloproteinases), aiding the promotion of infiltration and migration of cancer cells (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…In the later study the authors found that EZH2 expression was strongly associated with loss of the cell cycle suppressor protein p16 in melanomas and endometrial carcinomas and increased expression in cyclin D1 in melanomas [20] connecting their findings with uncontrolled cell cycle in cancer cells overexpressing EZH2. EZH2 expression in colorectal cancer was reported to positively associate with TNM stage and lymph node metastasis [21] while another study evaluating the role of EZH2 expression in gastrointestinal malignancies, found that its overexpression is correlated with poor prognosis in esophageal but not colorectal and gastric cancer [22]. Moreover, EZH2 has been strongly associated with advanced stage and poor prognosis in squamous cell malignancies including cervical cancer [23], esophageal squamous cell carcinoma [24] and head and neck cancer [25].…”
Section: Evidence Correlating Ezh2 Function With Cancermentioning
confidence: 99%
“…EZH2 methylates H3K27, which facilitates chromatin compaction and gene silencing (2). Several lines of evidence have implicated EZH2 in the development and progression of a variety of cancers, and elevated expression of EZH2 often correlates with a poor prognosis (3, 4). An early indication of a role for EZH2 in prostate cancer was based on the observation that EZH2 overexpression is associated with worse progression of prostate cancer (5).…”
Section: Introductionmentioning
confidence: 99%